Uji Kesesuaian Alat Proteksi Radiasi Berdasarkan Nilai Exposure Index (EI) di Rumah Sakit Bali Mandara - Chasbas Putra Tamba; Gusti Ngurah Sutapa; Ketut Putra; Nengah Sandi; I Wayan Gede Suharta; I Gde Antha Kasmawan (Kappa Journal, 2026)
A study has been conducted on the suitability test of radiation protection equipment based on the Exposure Index (EI) at Bali Mandara Hospital. The data used in this study are primary data obtained by conducting X-ray irradiation on PPE, namely Apron, Gonad Shield, thyroid Shield, gloves, and glasses using an X-ray machine. Then the irradiation results are processed using a CR system machine to obtain EI values using variations in tube voltage of 80 Kv, 100 Kv, 130 Kv, and a time current of 18 mAs. From the results of the analysis that has been carried out, the average EI value was obtained with a tube voltage of 80 kV for Apron 1004.60 ± 1.72, gonad shield 1302.80 ± 1.94, Thyroid shield 1444.60 ± 1.63, glasses 1375.40 ± 1.72, gloves 1478.60 ± 0.93, for a tube voltage of 100 kV the EI value for the apron was 1511.20 ± 1.24, gonad shield 1697.80 ± 1.65, thyroid shield 1810.60 ± 1.57, glasses 1598.60 ± 1.33, gloves 1819.40 ± 0.75, for a tube voltage of 130 kV 1831.00±1.41, gonad shield 2090.60±1.21, thyroid shield 2129.00±2.00, glasses 2980.20±1.07, gloves 2114.00±1.41. The EI value obtained using 80 kV tube voltage is still within the limits set by PERKA BAPETEN No.8 of 2011, namely 1300-1800